Toll-Like Receptor 2 Activation by β2→1-Fructans Protects Barrier Function of T84 Human Intestinal Epithelial Cells in a Chain Length–Dependent Manner. Issue 7 (30th April 2014) - Vogt, Leonie M.; Meyer, Diederick; Pullens, Gerdie; Faas, Marijke M.; Venema, Koen; Ramasamy, Uttara; Schols, Henk A.; de Vos, Paul
Abstract: Dietary fiber intake is associated with lower incidence and mortality from disease, but the underlying mechanisms of these protective effects are unclear. We hypothesized that β2→1-fructan dietary fibers confer protection on intestinal epithelial cell barrier function via Toll-like receptor 2 (TLR2), and we studied whether β2→1-fructan chain-length differences affect this process. T84 human intestinal epithelial cell monolayers were incubated with 4 β2→1-fructan formulations of different chain-length compositions and were stimulated with the proinflammatory phorbol 12-myristate 13-acetate (PMA). Transepithelial electrical resistance (TEER) was analyzed by electric cell substrate impedance sensing (ECIS) as a measure for tight junction–mediated barrier function. To confirm TLR2 involvement in barrier modulation by β2→1-fructans, ECIS experiments were repeated using TLR2 blocking antibody. After preincubation of T84 cells with short-chain β2→1-fructans, the decrease in TEER as induced by PMA (62.3 ± 5.2%, P < 0.001) was strongly attenuated (15.2 ± 8.8%, P < 0.01). However, when PMA was applied first, no effect on recovery was observed during addition of the fructans. By blocking TLR2 on the T84 cells, the protective effect of short-chain β2→1-fructans was substantially inhibited. Stimulation of human embryonic kidney human TLR2 reporter cells with β2→1-fructans induced activation of nuclear factor kappa-light-chain-enhancer of activated B cells, confirming that β2→1-fructans are specific ligands for TLR2. To conclude, β2→1-fructans exert time-dependent and chain length–dependent protective effects on the T84 intestinal epithelial cell barrier mediated via TLR2. These results suggest that TLR2 located on intestinal epithelial cells could be a target of β2→1-fructan–mediated health effects.